TINJAUAN YURIDIS TERHADAP PEMBIAYAAN MODAL VENTURA SYARI'AH TERHADAP USAHA MIKRO KECIL DAN MENENGAH (UMKM) DENGAN SISTEM PERHITUNGAN PROFIT SHARING - Edy Nurcahyo (Lembaga Penelitian dan Pengabdian Masyarakat, 2018)
The purpose of this research is to describe a legal review against syariah venture capital financing which given to business partner which in the form of micro business, small business, and medium enterprises with profit sharing. This research method is normative legal research. The main data source which is used is the literature. Researcher uses a conceptual approach because of adapts to the legal material under study, then it analyzed by qualitative analysis. The result of research shows that syariah venture capital financing have gined legal protection from positif law in Indonesia for doing financing based on prinsip's profit sharing. Every business operation of Syariah Venture Capital Financing and Syariah Business Unit must fulfill the principles of justice, equilibrium, benefit, and univeralism.